A view of the universe - Malin, David; Murdin, Paul 1942- (Cambridge Univ. Pr. u.a., 1993)
Malin weaves a lucid and highly informative description of each picture into a well-rounded view of our colourful Universe. After describing the advances made in astronomy through photography, he launches on a magnificent tour of the Universe, as seen through his camera lens. The constellation Orion, the star clouds of the Milky Way, and the glittering stars of the Jewel Box cluster introduce the starry realms